In-Vitro Antifungal Activity of Different Fraction of Juniperus Communis Leaves and Bark Against Aspergillus Niger and Aflatoxigenic Aspergillus Flavus - Pankaj kumar; R.P.Bhatt; O.P.Sati; Vinod Kumar Dhatwalia; Lokendra Singh (International Journal of Pharma and Bio Sciences, 2010)
The increasing resistance to antifungal compounds and the reduced number of available drugs led us to search therapeutic alternatives among aromatic plants and their essential oils, empirically used by antifungal properties. In present study different concentration of methanol, ethanol, chloroform, petroleum ether extracts of Juniper communis leaves extracts as well as bark extracts were studied against A.niger and aflatoxigenic A.flavus. It was found that among all leaf extracts,methanolic extract have maximum percentage growth inhibition (57.8%) against A.flavus,while ethanolic extract showed maximum percentage growth inhibition (56%) against A.niger.In case of bark extract,ethanolic extract have maximum percentage growth inhibition(48%) against A.flavus,while methanolic extract showed maximum percentage growth inhibition against A.niger(40%).